Character sketch : a drawing course for costume designers - Huang, Helen Q. (Routledge, 2018)
"Character Sketch outlines a theory of costume rendering that explores how a designer conceptualizes and creates a character on the page. Beginning with how to develop a sense of character through active, gestural poses, this book explores and explains the process of drawing and painting from rough sketch to finished rendering."--Publisher's description